Modelos digitales de elevación para el análisis de la precisión de La Región Caribe de Colombia (2022)
Digital elevation modeling (DEM) is the initial part for a number of methodology and spatial analysis models. This, since the extracted results are of high quality, this is due to to which it is linked with high quality of its spatial resolution.